2008
DOI: 10.1016/j.physbeh.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Satiating effects of protein but not carbohydrate consumed in a between-meal beverage context

Abstract: Previous research has suggested that protein is the most satiating macronutrient; however some experiments have found no difference in satiating efficiency of protein and carbohydrate during short intervals after consumption. There is also evidence that the satiating effects of carbohydrate are minimal when in a beverage rather than solid context. To evaluate whether protein-based satiety was evident in a drink context, and clarify further effects of preload time on satiety, the present study compared iso-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 62 publications
(92 reference statements)
4
84
0
4
Order By: Relevance
“…For example, protein is generally found to be more satiating than carbohydrate [e.g. 81,82], and fat has often been reported as least satiating [e.g. 83,84], although as with the learning studies reviewed here not all studies find evidence of differences in effects of macronutrients on satiety [85][86][87].…”
Section: Discussionmentioning
confidence: 99%
“…For example, protein is generally found to be more satiating than carbohydrate [e.g. 81,82], and fat has often been reported as least satiating [e.g. 83,84], although as with the learning studies reviewed here not all studies find evidence of differences in effects of macronutrients on satiety [85][86][87].…”
Section: Discussionmentioning
confidence: 99%
“…Protein is the most satiating macronutrient and protein-rich diets are known to exert beneficial effects on body composition and metabolism (Bertenshaw et al 2008;Chou et al 2012). Increasing numbers of studies are reporting that the protein fraction in diet is insufficient (for available sources are scarce and expensive).…”
Section: Introductionmentioning
confidence: 99%
“…Semi-skimmed milk and sucrose-sweetened soft drinks are isocaloric beverages (volume to volume) but because of their different macro-nutritional composition they may affect satiety in different ways Halton and Hu, 2004;Bertenshaw et al, 2008). Investigation of the effects of milk compared with sugar-sweetened soft drinks (SSSD) on appetite and energy intake (EI) seems warranted, as milk is considered to be part of a healthy diet, whereas SSSD has been associated with obesity development, which is suggested to be owing to lack of proper satiation induced by this beverage (DiMeglio and Mattes, 2000;Ludwig et al, 2001;Dubois et al, 2007;Leidy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dove et al (2009) showed that skim milk compared with a sugar-sweetened fruit drink decreased hunger and EI 4 h after consumption of the test drink. Sugary beverages may be less satiating than milk because of the content of protein or fat in milk (Fischer et al, 2004;Bertenshaw et al, 2008;Paddon-Jones et al, 2008;Dove et al, 2009) that might affect insulin and appetite-regulating hormones to a larger extent than carbohydrates and promote satiation to a larger degree (Foster-Schubert et al, 2008;Wolnerhanssen and Beglinger, 2010). However, other studies have failed to show decreased EI after milk compared with SSSD (Almiron- Roig and Drewnowski, 2003;DellaValle et al, 2005;Harper et al, 2007;Soenen and Westerterp-Plantenga, 2007).…”
Section: Introductionmentioning
confidence: 99%